2023
DOI: 10.7150/ijbs.84060
|View full text |Cite
|
Sign up to set email alerts
|

Ability of Local Clearance of Senescent Cells in Ipsilateral Hemisphere to Mitigate Acute Ischemic Brain Injury in Mice

Abstract: Senolytic treatment has potential therapeutic efficacy for acute ischemic stroke (AIS). However, the systemic treatment of senolytics may produce off-target side effects and a toxic profile, which affect analysis of the role of acute senescence of neuronal cells in pathogenesis of AIS. We constructed a novel lenti-INK-ATTAC viral vector to introduce INK-ATTAC genes to the ipsilateral brain and locally eliminate senescent brain cells by administering AP20187 to activate caspase-8 apoptotic cascade. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…This would be in line with the known function of senescence-associated secretory phenotype, where senescent cells secrete a collection of proinflammatory factors that lead to persistent low-grade tissue inflammation and injury 19 . However, the data presented in this manuscript do not rule out the possibility that other non-microglial senescent cells are being targeted by ABT-263 and contributing to the observed phenotype, as ABT-263 has been demonstrated in other studies to have profound effects on various senescent cell populations (Table 1 22,4757 ).…”
Section: Discussionmentioning
confidence: 61%
“…This would be in line with the known function of senescence-associated secretory phenotype, where senescent cells secrete a collection of proinflammatory factors that lead to persistent low-grade tissue inflammation and injury 19 . However, the data presented in this manuscript do not rule out the possibility that other non-microglial senescent cells are being targeted by ABT-263 and contributing to the observed phenotype, as ABT-263 has been demonstrated in other studies to have profound effects on various senescent cell populations (Table 1 22,4757 ).…”
Section: Discussionmentioning
confidence: 61%
“…Previous studies demonstrated that ABT-263, FOXO4-D-Retro-Inverso peptide, and a combination of dasatinib and quercetin modulated inflammatory response and eliminated senescent cells, thereby attenuating IR associated cardiac and renal injury [ 100 , 101 , 102 , 103 ]. However, ABT-263 has only been validated in animal model of ischemic stroke [ 77 , 83 ]. Senomorphs are agents that prevent cell cycle arrest, rather than eliminating senescent cells, and attenuate the secretion of SASP [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Immuno-histochemical analysis of an autopsy human brain sample showed that an increased p16 level was observed in the perimeter of the infarct area [ 33 ]. Similarly, increased mRNA expression of p16 , Il-6 , Ccl8 , and Cxcl2 were detected in the ipsilateral cortex, striatum, and hippocampus from 6-12h in a mouse model of MCAO [ 77 ]. Immuno-histochemical analysis revealed that increased expression of senescent markers was predominantly localized in astrocytes and endothelial cells rather than neurons and microglia in the ipsilateral region.…”
Section: Role Of Senescence/sasp In Ischemic Strokementioning
confidence: 99%
See 1 more Smart Citation
“… 54 , 55 Navitoclax has shown promise in eliminating senescent cells following cerebral IRI, reducing infarct volume, and improving neurological function in rats. 54 , 56 Also, chronic neuroinflammation mediated by senescent cells may exist following brain injury, especially traumatic. Senolytic therapy with intermittent D&Q was shown to be neuroprotective by reduction of SASP and subsequent attenuation of depressive symptoms and improved cognition.…”
Section: Systemic Atherosclerosis: Coronary Artery Disease Stroke And...mentioning
confidence: 99%